Mental health and life satisfaction in East and West Germany: Effects of generation and migration of citizens - Beutel, Manfred E.; Braunheim, Lisa; Heller, Ayline; Schmutzer, Gabriele; Decker, Oliver; Brähler, Elmar (Frontiers in Public Health, 2022)
Objective: Reunification of Germany after separation between 1949 and 1990 has offered a unique chance of studying the impact of socialization, political transformation, and migration on mental health. The purpose of this paper was to compare mental distress, resources, and life satisfaction 1) between residents of East and West Germany and migrants who have fled from East to West Germany before reunification; 2) between three generations. Methods: We assessed anxiety, depression, resilience, self-esteem, and life satisfaction, comparing groups based on their residency and migration as well as three different birth cohorts. Using a representative survey of 2006, analyses of variance show the differences between these groups. Based on a representative survey (N=4530), the effects of gender (53.6% females), residency/migration (74.4% grown up in the West, 20.4% in the East, 5.3% migrants from the East to the West) from three generations (32% born until 1945, 39% until 1967, and 29% to 1989), positive and negative mental health indicators were analyzed. Results: Women reported higher distress and lower resilience. Residents of the Western states reported the lowest burden of distress (depressive, anxiety symptoms) and the highest overall life satisfaction, exceeding residents from the Eastern states and migrants from the Eastern to Western states. Migrants from the Eastern to the Western states, however, reported the lowest resilience and self-esteem. They reported lower satisfaction with income, living conditions (compared to the Western residents) and the lowest levels of satisfaction with family (compared to East and West). Conclusions: Overall, our data point to inequalities between the Eastern and Western states regarding mental health sixteen years after reunification favoring the residents of the Western states by lower distress and life satisfaction. Our data attest to the stresses and adjustments associated with migration from the Eastern to the Western states before reunification. A lower level of mental health and life satisfaction in the oldest generation may be related to sequelae of World War II and also to aging.